Efficacy of a combined insecticide–rodenticide product on ectoparasite and commensal rodent mortality. Issue 3 (12th December 2020) - Hinds, Lyn A; Grice, David; Watson, Duncan M; Jacob, Jens
Abstract: BACKGROUND: Ectoparasites may transfer zoonotic pathogens from rodents to humans or livestock when rodents are managed with rodenticides. This could be minimized using a product combining a rodenticide with a delayed action and a systemic insecticide/acaricide that rapidly kills ectoparasites. Such a combination was tested in commensal pest rodent species to assess efficacy and timing of responses in rodents, and fleas and ticks feeding on them. Ticks or fleas attached to rats ( Rattus norvegicus ) and house mice ( Mus musculus domesticus ) were exposed to a product containing brodifacoum (50 ppm) and fipronil (40 ppm) for three days. RESULTS: 98–100% of fleas on treated rodents died within one to two days after first exposure, whereas >90% fleas survived on control rodents. The effect persisted for four or more days after bait uptake. Ticks started to succumb to the effect of the combination product within one day (mice) and within four days (rats) of first exposure, with all ticks dying by Day (D)8. Tick survival in control rodents was 90–100%. Rodent mortality began at D3 (rats) and D4 (mice) after first consumption of product and all were dead by D9 (rats) and D7 (mice). CONCLUSION: This product effectively killed ectoparasites and rodents. Flea mortality was swift and complete, generally within one day of exposure, whereas it took ticks up to four days to die, but before the rats and house mice died. The combination product might help to prevent ectoparasites migrating from dying rodents to another host. Field trials are warranted. © 2020 Society of Chemical Industry Abstract : The combination bait killed ectoparasites before rodents and should prevent ectoparasites migrating from dying rodents to humans/livestock. This can aid the protection of human/livestock health, stored produce and crops.